INVESTIGASI FAKTOR USIA MODALITAS MRI 1.5 TESLA TERHADAP SIGNAL TO NOISE RATIO - Dea Indri Utami; Irsal, Muhammad; Shinta Gunawati Sutori; Budiati, Tri Asih (Sekolah Tinggi Ilmu Kesehatan (STIKes) Cirebon, 2025)
Changes in signal-to-noise ratio (SNR) may be influenced by the installation age of MRI systems exceeding 10 years, as well as increased usage frequency, which can contribute to a decline in system performance. This study investigated the effect of MRI installation age on SNR in two different brands of 1.5 Tesla MRI systems. This research employed an experimental method by measuring SNR values using an MRI phantom filled with 1000 cc of water. Image acquisition was performed using FLAIR, DWI, and T2*GRE sequences. SNR measurements were conducted using ImageJ software with a consistent region of interest (ROI) diameter of 5 mm applied to all images. Statistical analysis was performed to assess differences in mean SNR values between the two 1.5 Tesla MRI systems using an independent samples t-test with a significance level of 0.05. The results showed that the SNR value for the FLAIR sequence was 102.8 for brand A and 65.8 for brand B, with a p-value of 0.00. For the DWI sequence, the SNR value was 63.4 for brand A and 54.3 for brand B, with a p-value of 0.04. For the T2*GRE sequence, the SNR value was 107.1 for brand A and 45.2 for brand B, with a p-value of 0.00. Differences in SNR values were associated with variations in acquisition parameters such as TR, TE, NEX, and bandwidth, differences in the number of head coil channels, as well as differences in production year and duration of MRI system utilization. Therefore, standardization of acquisition parameters, routine technical evaluation of MRI systems, and detailed analysis of DICOM metadata are recommended in future studies to achieve more objective and accurate comparisons of MRI image quality. Abstrak: Perubahan nilai signal to noise ratio (SNR) disebabkan faktor usia instalasi modalitas MRI yang sudah mencapai lebih dari 10 tahun, serta frekuensi penggunaan yang semakin tinggi yang dapat menyebabkan penurunan kinerja modalitas. Penelitian ini melakukan investigasi faktor usia instalasi modalitas MRI terhadap SNR pada dua merek modalitas MRI dengan kekuatan medan magnet 1.5 Tesla. Metode penelitian ini adalah eksperimen dengan melakukan pengukuran nilai SNR pada dua modalitas MRI menggunakan pantom MRI yang berisi air dengan volume 1000 cc pada penggunaan sequence FLAIR, DWI dan T2*GRE. Pengukuran SNR menggunakan Image-J dengan mempertimbangkan ukuran regoin of interest (ROI) berdiameter 5 mm sama pada semua citra. Kemudian dilakukan uji statistik untuk mengetahui adakah perbedaan nilai rata-rata SNR pada kedua modalitas MRI 1.5 Tesla dengan uji Independent t-test dengan nilai p-value 0.05. Hasil penelitian untuk nilai SNR pada sequence FLAIR untuk merek A 102.8, sedang merek B 65.8 dengan hasil p-value 0.00. Nilai SNR Pada sequence DWI untuk merek A 63.4, sedangkan merek B 54.3 dengan hasil p-value 0.04. Nilai SNR Pada sequence T2*GRE untuk merek A 107.1, sedangkan merek B 45.2 dengan hasil p-value 0.00. Perbedaan nilai SNR tersebut berkaitan dengan variasi parameter akuisisi seperti TR, TE, NEX, dan bandwidth, perbedaan jumlah channel head coil, serta perbedaan tahun produksi dan usia pemanfaatan perangkat MRI. Oleh karena itu, perlunya standarisasi parameter akuisisi, evaluasi teknis perangkat MRI secara berkala, serta analisis metadata DICOM pada penelitian selanjutnya guna memperoleh perbandingan kualitas citra MRI yang lebih objektif dan akurat.